Evaluación técnico financiera del uso de un raspador rotativo utilizado en operaciones de limpieza del revestimiento 7’’ en el pozo a2 ubicado en el campo hato nuevo (2018)
The Hato Nuevo Field is located in the Upper Magdalena Valley Basin of Colombia and is part of the fields managed by the Alto Magdalena Management of Ecopetrol S.A. Within the operations of maintenance and reconditioning of the wells in the Hato Nuevo Field, it has been identified that the cleaning power of the scrapers used has not been as expected, as there have been unplanned times for additional cleaning trips when they present obstructions during the descent of tools, mainly in the running of electrical registers and it is evident in the misinterpretation of these. Therefore, reality leads to another type of rotary movement scrapers, which present an improvement in the design with respect to the conventional scraper, because their blades are more resistant and fixed to the body of the tool, in addition to having metal bristles making the function of brushes, allow to achieve a better cleaning since they can be reciprocated and rotated simultaneously.